HUMBERT'S COPING METHOD IN "LOLITA" BY VLADIMIR NABOKOV - Okta Tri Umami; Nenden Rikma Dewi (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
Humbert-Humbert in â€œLolitaâ€ is portrayed as a man who admired young girls in his life due to his lack of affection during childhood. In order to fulfill the absence, Humbert has developed particular personality, which was being a well-mannered person. However, this personality was merely his way and Ego to interact with society. In addition, this personality was Humbertâ€™s method to cope and negotiate with his deepest passion since his individuality was bound with morality rules in his society. This paper applies descriptive-analytic method and adopts McLeodâ€™s ideas on Id, Ego and Superego to identify how Humbert coped with his deepest desire. From the discussion, this current research found that he managed himself by being a literature professor as well as a husband in order to fulfill his Id yet being tolerated with his superego. Thus, this particular personality was apparently projected as his coping method and his way to be a so-called good person in his society.